2022
DOI: 10.3390/polym14193971
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Gas Post-Curing and Printer Type on the Mechanical Properties of 3D-Printed Hard Occlusal Splint Material

Abstract: Although three-dimensional (3D) printing is clinically convenient to fabricate occlusal splints, it is still unclear how the post-curing method and the printer type can affect 3D-printed splints. This study aimed to evaluate the effect of stroboscopic post-curing at a nitrogen gas (N2) atmosphere versus post-curing in an air atmosphere, as well as the printer type (liquid crystal display (LCD) and digital light processing (DLP)) on the mechanical properties of a 3D-printed hard-type occlusal splint material. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 36 publications
4
33
0
Order By: Relevance
“…Finally, in accordance with the same manner as the first drying procedure, the second drying procedure was continued until a stable weight (WT 3 ) of each specimen was acquired. W SP and W SL were calculated in percentages (%) using the following equations [ 19 , 45 , 46 ]: W SP = [(WT 2 − WT 3 )/WT 1 ] × 100 and W SL = [(WT 1 − WT 3 )/WT 1 ] × 100 where WT 1 is the initial weight of the specimen after storing it in a desiccator for 24 h in milligrams (mg); WT 2 is the weight of the specimen after water immersion for 30 days in milligrams (mg); and WT 3 is the stable weight of the specimen after the second drying cycle in milligrams (mg).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in accordance with the same manner as the first drying procedure, the second drying procedure was continued until a stable weight (WT 3 ) of each specimen was acquired. W SP and W SL were calculated in percentages (%) using the following equations [ 19 , 45 , 46 ]: W SP = [(WT 2 − WT 3 )/WT 1 ] × 100 and W SL = [(WT 1 − WT 3 )/WT 1 ] × 100 where WT 1 is the initial weight of the specimen after storing it in a desiccator for 24 h in milligrams (mg); WT 2 is the weight of the specimen after water immersion for 30 days in milligrams (mg); and WT 3 is the stable weight of the specimen after the second drying cycle in milligrams (mg).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, digital technology has played an important role in various dental fields. The three-dimensional (3D) printing method is rapidly becoming more common in dental appliance fabrications, including occlusal splints [ 18 , 19 ]. This method provides 3D objects built by a layer-by-layer replication with two-dimensional (2D) data acquired with computer-aided designing (CAD) and computer-aided manufacturing (CAM) systems [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is followed by support removal and post-production curing with Cure M (Graphy, Seoul, Korea). The nitrogen generation curing unit has been utilized (28) and recommended to enhance the physical properties of the resin material by providing an inert environment, thereby preventing the formation of oxygen inhibition layer (37). THC 2 UV Curing system (Graphy Inc., Seoul, Korea) is a known representation of this category.…”
Section: Post-processingmentioning
confidence: 99%
“…Thanks to the increased light intensity, DLP printers can produce items more effectively, leading to the widespread development of dental materials for DLP-based stereolithography printing systems [ 17 , 18 ]. On the other hand, previous studies reported that LCD printers could provide objects with a smoother surface and a higher degree of conversion than DLP printers [ 19 , 20 ]. Although LCD printers might have several advantages, only a few studies have been performed on objects printed using LCD printers.…”
Section: Introductionmentioning
confidence: 99%